HIV‐1 coreceptor usage in paired plasma RNA and proviral DNA from patients with acute and chronic infection never treated with antiretroviral therapy. Issue 2 (20th August 2014) - Bon, I.; Turriziani, O.; Musumeci, G.; Clò, A.; Montagna, C.; Morini, S.; Calza, L.; Gibellini, D.; Antonelli, G.; Re, M. C.
<x xml:space="preserve">Abstract</x> Although an independent evolution of viral quasispecies in different body sites might determine a differential compartmentalization of viral variants, the aim of this paper was to establish whether sequences from peripheral blood mononuclear cells (PBMCs) and plasma provide different or complementary information on HIV tropism in patients with acute or chronic infection. Tropism was predicted using genotypic testing combined with geno2pheno (coreceptor) analysis at a 10% false positive rate in paired RNA and DNA samples from 75 antiretroviral‐naïve patients (divided on the basis of avidity index into patients with a recent or long‐lasting infection). A high prevalence of R5 HIV strains (97%) was observed in both compartments (plasma and PBMCs) in patients infected recently. By contrast, patients with a long‐lasting infection showed a quite different situation in the two compartments, revealing more (46%) X4/DM in PBMCs than patients infected recently (3%) (P = 0.008). As‐ a knowledge of viral strains in different biological compartments might be crucial to establish a therapeutic protocol, it could be extremely useful to detect not only viral strains in plasma, but also viruses hidden or archived in different cell compartments to better understand disease evolution and treatment efficacy in patients infected with HIV. J. Med. Virol. 87:315–322, 2015. © 2014 Wiley Periodicals, Inc.